2019
DOI: 10.1186/s12874-019-0777-x
|View full text |Cite
|
Sign up to set email alerts
|

Methodology and reporting characteristics of studies using interrupted time series design in healthcare

Abstract: Background Randomised controlled trials (RCTs) are considered the gold standard when evaluating the causal effects of healthcare interventions. When RCTs cannot be used (e.g. ethically difficult), the interrupted time series (ITS) design is a possible alternative. ITS is one of the strongest quasi-experimental designs. The aim of this methodological study was to describe how ITS designs were being used, the design characteristics, and reporting in the healthcare setting. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
169
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(176 citation statements)
references
References 7 publications
2
169
1
4
Order By: Relevance
“…Effectiveness of the program would be assessed by comparing parents who were close to the cutoff who were not ordered to divorce education against those who were. An interrupted time series design (Hudson, Fielding, & Ramsay, 2019) of divorce education would be another promising study design. Consider a situation in which all divorcing parents in a county have some sort of assessment or metric of healthy co‐parenting conducted.…”
Section: Resultsmentioning
confidence: 99%
“…Effectiveness of the program would be assessed by comparing parents who were close to the cutoff who were not ordered to divorce education against those who were. An interrupted time series design (Hudson, Fielding, & Ramsay, 2019) of divorce education would be another promising study design. Consider a situation in which all divorcing parents in a county have some sort of assessment or metric of healthy co‐parenting conducted.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the effectiveness of peer supervision among drug sellers on appropriate treatment of children less than ve years of age with pneumonia symptoms, uncomplicated malaria and non-bloody diarrhoea, interrupted time series for multiple group analysis was conducted [29]. The ITSA method was the preferred choice for this this study because it was not possible to randomise peer supervision (the intervention) [30]. In addition we wanted to cater for policy shifts if they occurred during the study period-a major strength of using interrupted time series [31].…”
Section: Discussionmentioning
confidence: 99%
“…Our search strategy has been informed by previous publications that have reviewed ITS studies 14 , 15 , 19 . Reviews of ITS studies will be identified using terms adapted from the search strategies of these publications and then combined with terms to identify meta-analyses and systematic reviews.…”
Section: Methodsmentioning
confidence: 99%
“…Reviews of ITS studies will be identified using terms adapted from the search strategies of these publications and then combined with terms to identify meta-analyses and systematic reviews. As there is little consistency in the terminology used to describe ITS studies 15 , 16 , our search terms are intentionally broad to achieve greater search sensitivity. Terms will be searched both as free text in the titles, abstracts and keywords fields, and as MeSH terms (or equivalent) where applicable.…”
Section: Methodsmentioning
confidence: 99%